The Role of Public Relations In Improving Environmental Quality Through Green Marketing Stuja Coffe Jakarta - Pradini, Gagih; Lutfiana, Hilya; Awaloedin, Dipa Teruna (Peneliti.net, 2024)
Tourism has become a basic need for hundreds of millions of people worldwide. Alongside the growth of the tourism industry, environmental issues have gained significant attention. The concept of Green Marketing has emerged as a potential strategy to enhance environmental quality and create a positive image in the tourism and culinary industries. This study evaluates the role of green marketing in improving environmental quality, focusing on the case study of Stuja Coffee Jakarta, and examines the public relations (PR) strategies used to promote and maintain a sustainable image. The research method used is a qualitative approach, involving direct observation at Stuja Coffee Jakarta, interviews with company directors, and analysis of documents and SWOT (Strengths, Weaknesses, Opportunities, Threats). The results indicate that Stuja Coffee has a strong commitment to green marketing by promoting environmentally friendly products, adopting sustainable practices, and reducing negative impacts on the environment. Through effective green marketing initiatives and innovative PR strategies, Stuja Coffee Jakarta strives to raise public awareness about environmental quality. The SWOT analysis identifies the strengths, weaknesses, opportunities, and threats faced by Stuja Coffee Jakarta in implementing its green marketing strategy. Strengths include a strategic location in the business and entertainment center of Jakarta and the ability to develop innovations in green marketing. Weaknesses relate to a lack of consumer awareness of green products. Opportunities include partnerships with environmental organizations and increasing consumer demand for eco-friendly products. Threats consist of fierce competition in the coffee industry, as well as criticism and controversy associated with business practices or green marketing. The study concludes that green marketing strategies and effective PR roles are essential for Stuja Coffee Jakarta to improve environmental quality and maintain a positive company image. Several strategic recommendations are proposed to strengthen the role of PR and increase the effectiveness of Stuja Coffee Jakarta's environmental initiatives, including enhancing education, collaborating with environmental organizations, and developing environment-based loyalty programs. By implementing these recommendations, Stuja Coffee Jakarta can strengthen its PR role in supporting efforts to improve environmental quality through green marketing, create sustainable positive effects, and build good relationships with consumers and the general public.